THE STUDY OF CONSUMER DISPUTE RESOLUTION AGENCY (BPSK) AND NON-GOVERNMENTAL ORGANIZATION FOR CONSUMER PROTECTION (LPKSM) BY MIXED METHODS - Nur Alisha Suherman; Megawati Simanjuntak; Anggi Mayang Sari; Irni Rahmayani Johan (Journal of Child, Family, and Consumer Studies, 2023)
Consumer protection institutions were built to help consumers fight for their rights. The purpose of this study is to analyze the form of consumer protection programs by the two institutions through the effectiveness of the powers, roles, and duties of the two institutions in handling consumer protection cases. The research method used is a combination of quantitative and qualitative research. The results showed that general knowledge about the UUPK tended to be very good so the attitude assessment of the performance carried out on BPSK and LPKSM was also good. BPSK is mandated to provide consumer protection through consumer dispute resolution, while LPKSM in helping consumers fight for their rights can provide advocacy assistance to consumers. In carrying out its main tasks, LPKSM has succeeded in providing understanding to the community compared to BPSK. The role in providing education and outreach is only LPKSM. The effectiveness of the two institutions is shown through the performance of the two institutions by the responsibilities that must be carried out by each institution (BPSK and LPKSM) with the full support of the Government to continue to achieve and realize consumer empowerment.